2019
DOI: 10.1109/jcn.2019.000033
|View full text |Cite
|
Sign up to set email alerts
|

Optimal status updating with a finite-battery energy harvesting source

Abstract: We consider an energy harvesting source equipped with a finite battery, which needs to send timely status updates to a remote destination. The timeliness of status updates is measured by a non-decreasing penalty function of the Age of Information (AoI). The problem is to find a policy for generating updates that achieves the lowest possible time-average expected age penalty among all online policies. We prove that one optimal solution of this problem is a monotone threshold policy, which satisfies (i) each new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 32 publications
2
42
0
Order By: Relevance
“…Fig. 9 shows that, when the arrival rate is less than 0.1 Mbps (0.5 Mbps) when K = 80 (20), the network experiences a higher average AoI. It also shows that increasing the arrival rate will lead to a better average AoI, up to a certain point (around 0.8 Mbps when K = 80 and 2 Mbps when K = 20), after which the average AoI starts increasing again.…”
Section: E Impact Of the Arrival Ratementioning
confidence: 92%
“…Fig. 9 shows that, when the arrival rate is less than 0.1 Mbps (0.5 Mbps) when K = 80 (20), the network experiences a higher average AoI. It also shows that increasing the arrival rate will lead to a better average AoI, up to a certain point (around 0.8 Mbps when K = 80 and 2 Mbps when K = 20), after which the average AoI starts increasing again.…”
Section: E Impact Of the Arrival Ratementioning
confidence: 92%
“…In [22], an EH transmitter is assumed to encode a message into the timings of the status updates. The age-energy tradeoff is explored in [23], where a finite-battery source is charged intermittently by Poisson energy arrivals. The timeliness-distortion tradeoff of an EHpowered system is investigated in [24].…”
Section: A Related Workmentioning
confidence: 99%
“…Moreover, there are other studies which consider AoI for source-to-destination link in specific scenarios [24][25][26][27][28][29][30]. For instance, the authors in [24] considered an energy harvesting source and optimized the AoI penalty in status update. In [26], the authors introduced the AoI into content update in a local cache, where they found that update rate in the cache is proportional to the square-root of items' popularity.…”
Section: Related Workmentioning
confidence: 99%